PENGARUH HUMAN ,ORGANIZATION,T ECHNOLOGY TERHADAP NET BENEFIT SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DI RUMAH SAKIT BHAYANGKARA MAKASSAR TAHUN 2025 - Akbar Anugrah Putra Rusli; Afriyana Amelia Nuryadin; Dian Ekawaty; Ali Imran (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Background, Hospital Management Information System (SIMRS) has been implemented at Bhayangkara Hospital Makassar since 2019 as part of an effort to improve operational efficiency and quality of health services. There are obstacles such as errors, namely Some humans do not really understand all the features and workflows of the system so they experience confusion in operation, lack of firm policies and effective communication within the organization between management and SIMRS users. Method, This study uses a quantitative design with a cross-sectional study approach. A sample of 197 respondents. Data were collected through a questionnaire that includes four main variables: Human, Organization, Technology, and Net-Benefit. Data analysis was carried out using the chi-square test to identify significant influences between independent and dependent variables. Results and Conclusions, this study shows that there is a significant influence of Human aspects (p = 0.001), Organization aspects (p = 0.005), and Technology aspects (p = 0.001) so it can be concluded that there is an influence of human, organization, technology on the net benefit of the Hospital Management Information System (SIMRS) at Bhayangkara Hospital Makassar. to the Bhayangkara Hospital Makassar, providing structured training and determining human resources according to competency, conducting periodic evaluations of the organization, improving technical support, developing technology and providing relevant information.